A Single Nucleotide Polymorphism in the Acetyl-coenzyme A Acyltransferase 2 (ACAA2) Gene is Associated With Milk Yield in Chios Sheep - Tzamaloukas, Ouranios; Orford, Michael R.; Hadjipavlou, G.; Chatziplis, Dimitrios G.; Koumas, Alkis; Mavrogenis, Andreas; Miltiadou, Despoina; Papachristoforou, Christakis (My University, 2012)
The objective of this work was to identify single nucleotide polymorphisms (SNP) in the ovine acetylcoenzyme A acyltransferase 2 (ACAA2) gene and investigate their association with milk production traits. Molecular characterization was accomplished by sequencing the entire coding region and the 3􀁣 and 5􀁣 untranslated regions (UTR) of the ACAA2 gene from individuals of the Chios sheep bred in Cyprus. All exons appeared to be monomorphic except for the last exon, for which a single SNP located in the 3􀁣 UTR of the gene (HM537015:g.2982T>C) was detected. Mixed model association analysis, using SNP data from 318 animals from 104 paternal half-sib families and firstlactation phenotype and pedigree information on 2,405 ewes revealed that this SNP was significantly associated with milk yield. The significance of the SNP effect persisted when milk yield information up to the third lactation was analyzed. Both alleles at the locus segregated at similar frequencies. The T allele was associated with increased milk yield and exhibited partial dominant action. Animals with the g.2982TT or g.2982CT genotype had significantly higher milk yield than those with the g.2982CC genotype, with the g.2982T allele having an additive effect of 13.4 (±4.7) kg and a dominance effect of 7.9 (±6.1) kg. Based on estimated allelic effects and sample allele frequencies, the g.2982T>C SNP explained 10% of the additive genetic variance for milk yield. A putative mode of action through nutrient metabolism is discussed.
Keywords: ACAA2 gene; Milk yield; Chios sheep breed; SNP marker